The art of peacemaking : political essays by István Bibó - Bibó, István (World thought in translation., 2015)
"István Bibó (1911-1979) was a Hungarian lawyer, political thinker, prolific essayist, and minister of state for the Hungarian national government during the Hungarian Revolution of 1956. This magisterial compendium of Bibó's essays introduces English-speaking audiences to the writings of one of the foremost theorists and psychologists of twentieth-century European politics and culture. Elegantly translated by Péter Pásztor and with a scholarly introduction by Iván Zoltán Dénes, the essays in this volume address the causes and fallout of European political crises, postwar changes in the balance of power among countries, and nation-building processes"--